2006
DOI: 10.1176/ps.2006.57.7.937
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care for Bipolar Disorder: Part II. Impact on Clinical Outcome, Function, and Costs

Abstract: Collaborative chronic care models can improve some long-term clinical outcomes for bipolar disorder. Functional and quality-of-life benefits also were demonstrated, with most benefits accruing in years 2 and 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 249 publications
(108 citation statements)
references
References 68 publications
1
105
0
2
Order By: Relevance
“…It may be that these patients differed systematically in some way from the patients in our study: the study by Bauer and colleagues (14,15) involved veterans and the study by Simon and colleagues (16) involved members of a managed care health organization (HMO). The Department of Veterans Affairs care setting and culture may facilitate higher participation and retention rates in clinical trials, whereas managed care populations are often healthier and less impaired.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…It may be that these patients differed systematically in some way from the patients in our study: the study by Bauer and colleagues (14,15) involved veterans and the study by Simon and colleagues (16) involved members of a managed care health organization (HMO). The Department of Veterans Affairs care setting and culture may facilitate higher participation and retention rates in clinical trials, whereas managed care populations are often healthier and less impaired.…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that individuals with more severe symptoms or a longer duration of illness may respond less well to psychosocial treatments for bipolar disorder, compared with individuals with illness of more recent onset or those who are euthymic (6,30). Alternatively, there may be factors related to receiving care for bipolar disorder in a community mental health center that impede treatment, that are not found in the Department of Veterans Affairs (14,15) or in staff model HMOs (16). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the importance of collaborative, team‐based care is increasingly recognized in managing BD. APNs, by their training and experience, are well suited to facilitate optimal patient care in collaboration with the other healthcare team members (Bauer et al., 2006; Chung et al., 2007). An especially important role for APNs within primary care lies in the care of the patient, while specialists manage the bipolar illness.…”
Section: Introductionmentioning
confidence: 99%